2011
DOI: 10.1108/09513551111163657
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the performance of water utility companies

Abstract: Purpose – The purpose of this paper is to carry out an analysis of Italian water utility companies to determine whether their performance was related to certain relevant variables that have been broadly discussed in the existing literature. Among these are ownership structure, size and diversification. In addition, the paper considers another variable – the geographical location. Design/methodology/approach – The paper reviewed the annual financial statements of 80 Italian water utility companies between 2004 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(46 citation statements)
references
References 58 publications
3
43
0
Order By: Relevance
“…This means that the hypothesis "the more efficient a Water Supplier Company is, the higher its performance will be" is accepted. This confirms a study by Guerrini et al (2011) which found that efficiency enables a company to get profit or have better prformance. This study also found that private Water Supplier Companies are more efficient compared to government-owned Water Supplier Companies because private companies emphasize more on efficiency since they are profit-oriented.…”
Section: The Influence Of Efficiency On Performancesupporting
confidence: 80%
“…This means that the hypothesis "the more efficient a Water Supplier Company is, the higher its performance will be" is accepted. This confirms a study by Guerrini et al (2011) which found that efficiency enables a company to get profit or have better prformance. This study also found that private Water Supplier Companies are more efficient compared to government-owned Water Supplier Companies because private companies emphasize more on efficiency since they are profit-oriented.…”
Section: The Influence Of Efficiency On Performancesupporting
confidence: 80%
“…Most studies confirm the presence of economies of scale in the water industry [11][12][13], but others highlight diseconomies of scale in various countries [14][15][16][17][18][19][20].…”
Section: Literature Reviewmentioning
confidence: 86%
“…While there is considerable evidence that economies of scope exist for water production and distribution [4], results from studies on joint water and wastewater services differ. Studies focused mainly on the United Kingdom and Portugal [4,12] revealed contrasting results. Some scholars [26,27] highlighted economies of scope, while a more recent study [28] underlined the existence of diseconomies of scope.…”
Section: Literature Reviewmentioning
confidence: 98%
“…In other studies, various other indicators were observed. Sector impacts, sector concentration, product differentiation and stage of life cycle (Caloghirou, Protogerou, Spanos, & Papagiannakis, 2004); ownership structures, size, degrees of diversification and geographical location (Guerrini, Romano, & Campedelli, 2011); country effects (Goldszmidt, Brito, & de Vasconcelos, 2011); differences of government, trade policies, technology levels, internal competition and culture (Ketelhöhn & Quintanilla, 2012); firm strategy and the industry structure (Karabag & Berggren, 2014); market power and more efficient operation (Canarella, Miller, & Nourayi, 2013); lagged profitability, growth, productivity, firm age and industry affiliation (Yazdanfar, 2013) were used as indicators to explain the relationship with corporate profitability.…”
Section: The Relationship Between Profitability and Macroeconomic Indmentioning
confidence: 99%